A carbon nanotube coated metawall with ultra-wideband perfect wave absorption utilizing cement dielectric. (30th August 2022) - Wang, Xiaoran; Li, Qinghua; Lai, Haoxin; Xu, Shilang
Abstract: Metamaterials (MMs) have attracted intense attention owing to their unprecedented control over the propagation of electromagnetic waves. Researches on MMs usually concentrate on the metallic resonators layer, while the carbon materials-based resonators and the dielectric layer of MMs are relatively overlooked. Here, a novel and simple "metawall" perfect MM absorber based on carbon nanotube (CNT) is conducted, which enables ultra-wideband perfect absorption, showing three peaks with 99% absorption and yielding over 97% absorption in 5.6–11.0 GHz. A reproducible and cost-efficient fabrication method is proposed, using CNT paste as the resonator and the combination of lossy cement board and lossless ceramic fiberboard as the dielectric. Moreover, only one kind of one-dimensional gratings CNT pattern is required to achieve multi-band perfect absorption. Through the control experiments to investigate the roles of the components of the metawall structure, it is found that the wideband perfect absorption of the metawall can be attributed to its unique structure and the absorption performance of the cement board. The proposed metawall provides a new perspective for achieving wideband perfect absorption and may serve as a promising platform to combine carbon nanomaterials with practical load-bearing engineering components. Graphical abstract: We propose a novel and simple "metawall" perfect MM absorber based on CNT resonator and cement dielectric. A coatable CNT resonator and a simple fabrication method is presented. The metawall employees a special multilayer structure, achieving three peaks with near-unity absorption and yielding over 97% absorption in 5.6–11.0 GHz. A simple 1D CNT gratings pattern is required to achieve multi-band perfect absorption, which usually requires multiple resonators in traditional MMs. Image 1